Analisis Kelayakan Bisnis Platform Digital untuk Edukasi Gaya Hidup Sehat : Studi Kasus di Indonesia - Indah Setiarini; Naufal Fauzan Hasibuan; Tengku Syalia Faradiva; Tia Novira Sucipto (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study investigates the business feasibility of a digital platform designed to promote healthy lifestyle education in Indonesia. In light of growing public awareness regarding physical and mental well-being, interactive digital platforms have emerged as a strategic tool—serving both educational and market innovation purposes. Using a case study approach, the research examines market readiness, financial projections, technological infrastructure, and operational capabilities. Data collection methods include online surveys, stakeholder interviews, and comparative analysis of similar platforms. The feasibility assessment relies on SWOT analysis and Net Present Value (NPV) calculations to evaluate sustainability and profitability. Findings indicate significant market interest, especially in features related to health tracking and user-friendly experiences. Despite promising financial indicators (positive NPV and break-even point in the third year), challenges remain in brand awareness and user acquisition strategies. Opportunities for collaboration with wellness communities and health institutions further strengthen the platform’s long-term potential. This research provides a strategic foundation for developers, investors, and scholars interested in digital health entrepreneurship. It highlights the importance of user-centered design, adaptive monetization models, and integrated branding strategies to ensure viability and impact.